2014
DOI: 10.1017/jgc.2013.28
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Counsellors Providing Online Chat Counselling to Young People

Abstract: Online counselling is a rapidly growing field and, while there is emerging evidence of its comparative effectiveness, there has been little research into what techniques are being applied in practice and which clients will most likely benefit from this medium. Using a focus group methodology, this study examines the experiences of 19 online clinicians employed by a youth mental health service, investigating their perception of online clients, views on their counsellor roles, the approaches and techniques they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 28 publications
3
36
0
2
Order By: Relevance
“…This, in turn, provided them with a heightened sense of psychological safety as they no longer had the sense of being in the physical presence of intimidating authority figures. This finding was supported by previous research showing that both adult and young clients above the age of 12 years were primarily motivated to seek help online because of the emotional safety provided by the anonymous nature of the counselling process (Bambling et al, 2008;Barak et al, 2009;Cook & Doyle, 2002;Dowling & Rickwood, 2014a;Dunn, 2012;Fukkink & Hermanns, 2009a, 2009bHaberstroh et al, 2007;King et al, 2006a;Leibert et al, 2006;Mallen et al, 2005;Mallen et al, 2011;Perle et al 2011;Rochlen et al, 2004;Rodda et al, 2013;Suler, 2004;Young, 2005). This anonymity led to the reduction in perceived power difference between adult and child online, as compared to the traditional face-toface setting, thus facilitating expressions of emotional distress and self-assertion (Bambling et al, 2008).…”
Section: Impact Of Missing Non-verbal Cuessupporting
confidence: 71%
See 2 more Smart Citations
“…This, in turn, provided them with a heightened sense of psychological safety as they no longer had the sense of being in the physical presence of intimidating authority figures. This finding was supported by previous research showing that both adult and young clients above the age of 12 years were primarily motivated to seek help online because of the emotional safety provided by the anonymous nature of the counselling process (Bambling et al, 2008;Barak et al, 2009;Cook & Doyle, 2002;Dowling & Rickwood, 2014a;Dunn, 2012;Fukkink & Hermanns, 2009a, 2009bHaberstroh et al, 2007;King et al, 2006a;Leibert et al, 2006;Mallen et al, 2005;Mallen et al, 2011;Perle et al 2011;Rochlen et al, 2004;Rodda et al, 2013;Suler, 2004;Young, 2005). This anonymity led to the reduction in perceived power difference between adult and child online, as compared to the traditional face-toface setting, thus facilitating expressions of emotional distress and self-assertion (Bambling et al, 2008).…”
Section: Impact Of Missing Non-verbal Cuessupporting
confidence: 71%
“…The lack of non-verbal cues was challenging for the TCPs because they were not able to use the client's body language as a way to obtain feedback on how well their sessions were progressing. They were also unable to gauge the efficacy of their counselling using follow-up sessions -a phenomenon previous studies found was not uncommon in online counselling with young people, who tended to access online counselling only once or twice to obtain immediate support (Dowling & Rickwood, 2014a). It would, therefore, appear that, from the client's perspective, online counselling might serve the purpose of obtaining symptomatic relief rather than working on deep-seated issues.…”
Section: Impact Of Missing Non-verbal Cuesmentioning
confidence: 87%
See 1 more Smart Citation
“…One of the limitations of an online working environment is the loss of non‐verbal cues relating to emotion and the loss of contextual information as a result of the textual communication (Van de Luitgaarden, & Van der Tier, ; Beattie, Cunningham, Jones, & Zelenko, ). Ethical issues and the relatively time‐consuming textual communication, which forces social workers to be selective and focused in their use of language, are further limitations of an online working environment (Dowling & Rickwood, ; Peláeza, Garcíab, & Massóc, ). The advantages of an online working environment are anonymity and the low threshold of online platforms, which stimulate users to share emotionally distressing information and make it possible to reach a harder‐to‐reach target group (Bryant et al, ; Cipolletta, Votadoro, & Faccio, ; Mallen, Jenkins, Vogel, & Day, ).…”
Section: Introductionmentioning
confidence: 99%
“…Van de Luitgaarden, & Van der Tier, ; Bocklandt, Zitter, de Saelens, Zitter, Saelens, & Saelens, ; Vanhove & Vercaigne, ; Vlaeminck, Vanhove, Zitter, & Bocklandt, ). More studies are needed to critically evaluate the specific utility of online methods and online interventions to improve the knowledge base of online working methods in online social work (Dowling & Rickwood, ; Peláeza et al, ). This paper addresses this gap by reporting on the findings of a Dutch case study of the online intervention “Clickforhelp,” which was inspired by a solution‐focused approach ( Klikvoorhulp ).…”
Section: Introductionmentioning
confidence: 99%